2022
DOI: 10.1007/s12021-022-09565-8
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls and Recommended Strategies and Metrics for Suppressing Motion Artifacts in Functional MRI

Abstract: Information sharing statementThis work uses publicly available datasets, which are listed with hyperlinks in the Data Availability Statement. Code used for these analyses can be accessed through the hyperlink provided in the Methods.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…We found that static intrinsic FC metrics are mostly robust across motion denoising strategies in both young healthy controls and Parkinson’s participants. This is consistent with and supports previous studies 44,45 . However, dynamic FC metrics were very sensitive to denoising methods, in both groups but critically in the PD group.…”
Section: Discussionsupporting
confidence: 94%
“…We found that static intrinsic FC metrics are mostly robust across motion denoising strategies in both young healthy controls and Parkinson’s participants. This is consistent with and supports previous studies 44,45 . However, dynamic FC metrics were very sensitive to denoising methods, in both groups but critically in the PD group.…”
Section: Discussionsupporting
confidence: 94%
“…We also found that VG features were most sensitive to motion when more than 20% of the data was contaminated by framewise displacement of more than 0.2. This level of sensitivity to motion is consistent with previous research showing a strong association between functional network features and framewise motion in fMRI data (Raval et al, 2022 ). VGs are particularly sensitive to the presence of outliers and large values in the data, which is typical of what happens when there are motion events in fMRI.…”
Section: Discussionsupporting
confidence: 92%
“…If head motion phenotype truly has no relationship with any functional connection, then QC-FC could be used a measure of validity, with lower-magnitude QC-FC indicating more effective data cleaning. Although commonly used, QC-FC has been criticized because in-scanner movement may relate to neural patterns of interest and because it does not consider signal loss ( Raval et al, 2022 ; Williams et al, 2022 ). Williams et al (2022) observed that QC-FC behaved in unexpected ways when the FD cutoff for motion scrubbing was varied.…”
Section: Methodsmentioning
confidence: 99%